2012 Frontiers in Education Conference Proceedings 2012
DOI: 10.1109/fie.2012.6462392
|View full text |Cite
|
Sign up to set email alerts
|

Using practice theory to investigate professional engineers' workplace learning

Abstract: This paper reports on the first phase of an Australian inter-disciplinary partnership study concerned with professional learning of experienced engineers. It is a theoretically motivated, qualitative paper that aims to produce detailed descriptions of professional learning that arise within professional engineering work. The paper uses practice theory to conceptualise professional learning. By using 'practices' as the units of analysis, professional learning is understood as an integral part of everyday work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These gaps reflect the dominant focus on engineering science and analytical techniques in engineering degrees, from the latter half of the 20 th Century, and educators' lack of understanding of engineering practice (Trevelyan, 2010) as a socio-technical profession requiring capabilities that are both technical and social in nature (Leydens, 2012). Investigating the learning of experienced engineers in the workplace, Rooney et al (2012) found that they learned through situated, relational, collective practices engaging with team members who are in diverse roles. In formulating four principles for the redesign of engineering education, Sheppard, Macatangay, Colby, and Sullivan (2009) have recommended that engineering practice should be central to engineering education, with their third principle being: integrate identity, knowledge, and skills through approximations to practice (p. 200).…”
Section: Theoretical Framework and Modelmentioning
confidence: 99%
“…These gaps reflect the dominant focus on engineering science and analytical techniques in engineering degrees, from the latter half of the 20 th Century, and educators' lack of understanding of engineering practice (Trevelyan, 2010) as a socio-technical profession requiring capabilities that are both technical and social in nature (Leydens, 2012). Investigating the learning of experienced engineers in the workplace, Rooney et al (2012) found that they learned through situated, relational, collective practices engaging with team members who are in diverse roles. In formulating four principles for the redesign of engineering education, Sheppard, Macatangay, Colby, and Sullivan (2009) have recommended that engineering practice should be central to engineering education, with their third principle being: integrate identity, knowledge, and skills through approximations to practice (p. 200).…”
Section: Theoretical Framework and Modelmentioning
confidence: 99%
“…Sociomaterial approaches are also associated with questions regarding knowledge (Gherardi, ). Professionals must not only apply knowledge, they also have to participate in producing and sharing new knowledge (Rooney et al., ). Our use of the term ‘knowledge sharing’ reflects aspects of a general idea of how what one person or group of people knows becomes available to others.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Instead the approaches emphasize how learning is embodied in dynamic relationships among people and their physical contexts and are associated with questions regarding knowledge (Gherardi, 2009). Professionals must not only apply knowledge; they also have to participate in producing and sharing new knowledge (Rooney, et al, 2012). Professional knowledge and knowledge strategies are complex and are changing in the area of professional practice and work because of shifts in arrangements and responsibilities between professionals (Fenwick, Nerland & Jensen, 2012).…”
Section: Rationale For the Thesismentioning
confidence: 99%
“…Instead, knowledge is something that is emergent, a property of re-lationships between professionals. Within this perspective, learning between professionals can then be seen as a part of knowing-in-practice (Rooney et al, 2012). This perspective on knowledge and learning is of interest when investigating interprofessional education and collaboration in health care.…”
Section: Professional and Interprofessional Learningmentioning
confidence: 99%